Semaphorin‐3C signals through Neuropilin‐1 and PlexinD1 receptors to inhibit pathological angiogenesis - Yang, Wan-Jen; Augustin, Hellmut; Fischer, Andreas (EMBO molecular medicine, 2015)
Retinopathy of prematurity causes visual impairment due to destructive neoangiogenesis after degeneration of the retinal microvasculature. This study was aimed at analyzing whether local delivery of Semaphorin‐3C (Sema3C) suppresses pathological retinal angiogenesis. Sema3C exerted potent inhibiting effects in cellular models of angiogenesis. In an endothelial cell xenotransplantation assay, Sema3C acted primarily on immature microvessels by inducing endothelial cell apoptosis. Intravitreal administration of recombinant Sema3C disrupted endothelial tip cell formation and cell-cell contacts, which led to decreased vascular bed expansion and vessel branching in the growing retinal vasculature of newborn mice, while not affecting mature vessels in the adult retina. Sema3C administration strongly inhibited the formation of pathological pre‐retinal vascular tufts during oxygen‐induced retinopathy. Mechanistically, Sema3C signaled through the receptors Neuropilin‐1 and PlexinD1, which were strongly expressed on vascular tufts, induced VE‐cadherin internalization, and abrogated vascular endothelial growth factor (VEGF)‐induced activation of the kinases AKT, FAK, and p38MAPK. This disrupted endothelial cell junctions, focal adhesions, and cytoskeleton assembly resulted in decreased cell migration and survival. Thus, this study identified Sema3C as a potent and selective inhibitor of pathological retinal angiogenesis. See also: G Serini & L Tamagnone (October 2015); Synopsis: Semaphorin‐3C is a potent and selective inhibitor of pathological retinal angiogenesis that acts by signaling through Nrp‐1 and PlexinD1 receptors. The neural guidance molecule Semaphorin‐3C impairs the integrity of endothelial cell junctions and cell survival by signaling through the Nrp‐1 and PlexinD1 receptors.Nrp‐1 and PlexinD1 are highly expressed in growing blood vessels and these immature vessels are specifically targeted by Semaphorin‐3C.Pathological angiogenesis in a model of retinopathy of prematurity is curbed by local administration of recombinant Semaphorin‐3C protein.